Metagenomic characterization of sphingomyelinase C in the microbiome of humans and environments - Jeon, Jehyun; Kang, Seunghun; Hur, Junho K.; Rho, Mina (Frontiers in Cellular and Infection Microbiology, 2022)
Bacterial sphingomyelinases (SMases) hydrolyze sphingomyelin and play an important role in membrane dynamics and the host immune system. While the number of sequenced genomes and metagenomes is increasing, a limited number of experimentally validated SMases have been reported, and the genomic diversity of SMases needs to be elucidated extensively. This study investigated the sequence and structural characteristics of SMases in bacterial genomes and metagenomes. Using previously identified SMases, such as the β-toxin of Staphylococcus aureus, we identified 276 putative SMases and 15 metagenomic SMases by a sequence homology search. Among the predicted metagenomic SMases, six non-redundant metagenomic SMases (M-SMase1−6) were selected for further analysis. The predicted SMases were confirmed to contain highly conserved residues in the central metal-binding site; however, the edge metal-binding site showed high diversity according to the taxon. In addition, protein structure modeling of metagenomic SMases confirmed structural conservation of the central metal-binding site and variance of the edge metal-binding site. From the activity assay on M-SMase2 and M-SMase5, we found that they displayed sphingomyelinase activity compared to Bacillus cereus SMase. This study elucidates a comprehensive genomic characterization of SMases and provides insight into the sequence-structure-activity relationship.